WEB-BASED DECISION SUPPORT SYSTEM FOR EXAMPLE TEACHER SELECTION IN DIMU KALIPE SDK USING THE SIMPLE ADDITIVE WEIGHITE (SAW) METHOD - Marten Dara Rode; Adelbertus Umbu Janga; Paulus Mikku Ate (JTH: Journal of Technology and Health, 2023)
A school requires quality human resources and quality education in order to increase its profile and performance in achieving school educational targets and goals. One element that has a big influence is school quality. Therefore, a method or supervisory body is needed to assess the quality of education in schools while reducing subjective assessments of the quality of school education. Assessing the quality of school education certainly has many assessment criteria with different priorities, so an SPK application and method is needed that can take these criteria into account. One method of approach to solving multi-criteria problems is Simple Additive Weighite (Saw), which is a way of making decisions by looking for the best choice among existing alternatives by calculating the proximity of the alternative to the ideal solution value. The research was carried out by calculating the criteria points for quality elements and instruments so that it is easier to assess school quality. The final result obtained is a sequence of alternative closeness values ​​with the ideal solution value. From the test it can be concluded that it is easier to make more objective decisions.